Artificial intelligence and the transformation of online education: a case study of “MASTER OF STUDIES IN DIGITAL EDUCATION” program of university of guanajuato - Gurieva, N.; Reyes Espino, V. M.; Jimenez Arredondo, V. H. (ТОВ «Друкарня Мадрид», 2025)
The integration explores the impact of artificial intelligence (AI) on the transformation of online education through a case study of a master’s program in Digital Education at the University of Guanajuato. The study examines the theoretical foundations for integrating AI into the educational process. It analyses the potential of AI to personalize learning, automate routine tasks, create intelligent learning systems, and improve the digital competencies of program graduate’s students. The objective is to examine the potential for applying AI technologies in the master's program in Digital Education at the University of Guanajuato, including the adaptation of educational content, the use of generative AI to support students and assessment tools, and the development of appropriate strategies, teacher training, and the creation of assessment systems that take into account the specificities of AI use. Along with the benefits, the paper also details the challenges and risks associated with introducing AI into online education, such as ethical dilemmas, academic integrity issues when using generative AI, the need to develop critical thinking, and adapt the role of the teacher. The paper concludes by offering recommendations for the effective and ethical integration of AI technologies into online education, emphasizing the importance of teacher training, the development of appropriate policies, and maintaining a balance with traditional teaching methods to ensure a quality educational experience.
Keywords: artificial intelligence; theoretical foundations